Social institutions: the role and functions in the life of society - Кінаш, І. П.; Мацькевич, О. ч Ю. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2015)
In the article the role of social institutions in the process of transformations in the country is defined. Education, science and culture are accentuated among social institutions. The system of social principles, values, functions, which are realized through them, is considered. Its is suggested to consider social institutions as a stabilizing factor of the society.